Consumption of Food and Non-Food Manufactured Goods by Collective Farmers of Bashkiria in 1946—1950 - V. N. Mamyachenkov; V. P. Motrevich; A. L. Anisimov (Научный диалог)
The problems of providing collective farm families of the Bashkir Autonomous Soviet Socialist Republic with food and non-food industrial goods in the first post-war five-year period are studied. The relevance of the study is due to the unresolved problem of scientifically based and balanced consumption of these goods by the population to date. The source base for writing the article was the materials of budget surveys of the population, which have a long history in our country. Materials from the funds of two archives, some of which have never been published and have signs of scientific novelty were used. It was alleged that the main foodstuffs in the Bashkir village in the first post-war years were potatoes, milk and bread with some addition of vegetables and meat products. It is stated that most of the money allocated for the purchase of manufactured goods was spent on the purchase of ready-made clothes, shoes, fabrics and piece goods from them, as well as soap and matches. Attention is focused on the fact that the monetary reform of 1947 sharply reduced the income of collective farmers in the Urals. It is proved that in the period under study the level of provision of collective farm families of the Bashkir Autonomous Soviet Socialist Republic with food and nonfood industrial goods was significantly lower than the scientifically based norms for their consumption.